A Novel Therapeutic Approach With Sodium Pyruvate on Vital Signs, Acid–Base, and Metabolic Disturbances in Rats With a Combined Blast and Hemorrhagic Shock - Saha, Biswajit; Sahu, Geetaram; Sharma, Pushpa (Frontiers in Neurology, 2022)
Background: Blast injuries from improvised explosive devices (IEDs) are known to cause blast traumatic brain injuries (bTBI), hemorrhagic shock (HS), organ damage, mitochondrial dysfunction, and subsequent free radical production. As a pre-citric acid cycle reagent, pyruvate is suggested to improve mitochondrial ATP production through the activation of mitochondrial gate keeper enzyme “pyruvate dehydrogenase complex (PDH)”. Our study aimed to investigate the role of physiologic, metabolic and mitochondrial effects of hypertonic sodium pyruvate resuscitation in rats with combined blast and HS injury. Methods: Pre-clinical rat model of combined injury with repetitive 20 PSI blast exposure accompanied with HS, and fluid resuscitation (sodium pyruvate as metabolic adjuvant or hypertonic saline as control), followed by transfusion of shed blood was used in this study. Control Sham animals (instrumental and time-matched) received anesthesia and cannulation, but neither received any injury nor treatment. The mean arterial pressure and heart rate were recorded throughout the experiment by a computerized program. Blood collected at T0 (baseline), T60 (after HS), and T180 (end) was analyzed for blood chemistry, and mitochondrial PDH enzyme activity. Results: Sodium pyruvate resuscitation significantly improved the mean arterial pressure (MAP), heart rate (HR), pulse pressure (PP), hemodynamic stability (shock index), and autonomic response (kerdo index) after the HS and/or blast injury. Compared with base line values, plasma lactate, lactate/pyruvate ratios were significantly increased. In contrast, base excess BE/(HCO3-) was low, and the pH was also acidotic <7.3, indicating the sign of metabolic acidosis after blast and HS in all animal groups. Sodium pyruvate infusion significantly corrected these parameters at the end of the experiment. The PDH activity also improved after the sodium pyruvate infusion. Conclusion: In our rat model of combined blast and HS injury, hypertonic sodium pyruvate resuscitation was significantly effective in the hemodynamic stabilization through the correction of acid-base status and mitochondrial mechanisms via its pyruvate dehydrogenase enzyme.